"That's your right as a human isn't it?" The emergence and development of leading as a socially-just practice in early childhood education. Issue 4 (December 2020) - Gibbs, Leanne
This article reports on an Australian study of the emergence and development of leadership that supports children's rights and their access to high-quality early childhood education (ECE). The qualitative study contributes to a growing body of research on ECE leadership practice; specifically, the area of site-based leadership cultivation and development. Complexity leadership theory was used to situate leadership within the Australian ECE context; accounting for the competing purposes of high-quality education programs and for the complex array of practices required for leadership to be effective. Additionally, the theory of practice architectures was employed as an analytical tool. The theory of practice architectures helped to identify socially-just leadership practices that uphold children's rights, and to understand the organisational arrangements that enabled and constrained those practices within each site. Study findings illuminate how leadership can be cultivated and developed in ECE. As a result of the study, organisations are encouraged to create the cultural-discursive, material-economic and social-political arrangements that shape leadership within ECE sites. The paper argues for the development of ECE leadership as a socially-just practice, that upholds the rights of children and their access to high-quality early childhood education.